The Influence of Trust and Satisfaction on Customer Loyalty of School Bus Transportation Users in Bantaeng Regency - Dian Muhammad Rudi (Yayasan Amerta Insan Unggul, 2023)
The research conducted aimed to explore strategies for enhancing customer loyalty among school bus transportation users in Bantaeng Regency. Employing a quantitative approach, the study involved 90 respondents as its sample size. Data were gathered through the administration of questionnaires, a common method in survey-based research. Subsequently, the data underwent analysis utilizing multiple linear regression tests to ascertain patterns and relationships. The findings of the study revealed several key insights. Firstly, it was discovered that customer trust plays a crucial role in shaping customer loyalty within the context of school bus transportation services in Bantaeng Regency. The analysis indicated a significant and positive correlation between customer trust and loyalty, suggesting that when customers have confidence in the reliability and safety of the transportation service, they are more likely to exhibit loyalty by continuing to utilize it. Secondly, the study also identified customer satisfaction as another significant determinant of customer loyalty in the same setting. The results illustrated a positive and substantial relationship between customer satisfaction and loyalty, underscoring the importance of providing high-quality service experiences to foster loyalty among school bus transportation users in Bantaeng Regency. In summary, the research underscores the critical role of both customer trust and satisfaction in driving loyalty among school bus transportation users. These findings provide valuable insights for transportation service providers in Bantaeng Regency, suggesting that efforts to enhance trustworthiness and satisfaction levels can lead to greater customer loyalty, ultimately contributing to the long-term success and sustainability of school transportation services in the region.